5x+4(x-13)=5(x-8)

Simple and best practice solution for 5x+4(x-13)=5(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+4(x-13)=5(x-8) equation:


Simplifying
5x + 4(x + -13) = 5(x + -8)

Reorder the terms:
5x + 4(-13 + x) = 5(x + -8)
5x + (-13 * 4 + x * 4) = 5(x + -8)
5x + (-52 + 4x) = 5(x + -8)

Reorder the terms:
-52 + 5x + 4x = 5(x + -8)

Combine like terms: 5x + 4x = 9x
-52 + 9x = 5(x + -8)

Reorder the terms:
-52 + 9x = 5(-8 + x)
-52 + 9x = (-8 * 5 + x * 5)
-52 + 9x = (-40 + 5x)

Solving
-52 + 9x = -40 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-52 + 9x + -5x = -40 + 5x + -5x

Combine like terms: 9x + -5x = 4x
-52 + 4x = -40 + 5x + -5x

Combine like terms: 5x + -5x = 0
-52 + 4x = -40 + 0
-52 + 4x = -40

Add '52' to each side of the equation.
-52 + 52 + 4x = -40 + 52

Combine like terms: -52 + 52 = 0
0 + 4x = -40 + 52
4x = -40 + 52

Combine like terms: -40 + 52 = 12
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| V(2v-1)=0 | | 4y(2y-3x)-2x(x-3y)= | | (-9)[3+3]-12= | | 8n+16.2=1.825 | | 22.5+7.5= | | 3/2(x-5)=/6 | | x(3x-5)=(3x+6)(x-3) | | 6(x-8)=12(x+4) | | 3n+5n+2+n= | | (4q+9)(4q+9)=0 | | 4(x+3)=2x+10+2x | | 46/63-5/7 | | 57+57+123+x=360 | | 5+3(y-4)=5(y+3)-y | | -9+6-12= | | 5+7g=54 | | 12x+17x-6+5=-5x+5-6 | | 63=9(2-w) | | 6-4(5p+9)+3(2+p)=-18 | | 3t-18=4(-3-3/4) | | -6x+5(1)=1 | | 6n=64 | | 4.6x-14.6=5.4 | | 2(n+n+1)=(n+2)-36 | | 3/5x-2=1/5 | | 10y(y+2)+3x=5(3-x) | | 4y-2(x-y)= | | 5x-3x+16=-x+8 | | 9w-8=64 | | 5.50-3.75= | | 8+2x+3-x=2+1 | | (3/x)-2=11 |

Equations solver categories